Analysis of the two-point wheel-rail contact scenario using the knife-edge-equivalent contact constraint method. (June 2020) - Aceituno, Javier F.; Urda, Pedro; Briales, Eduardo; Escalona, José L.
Highlights: A simplified online wheel-rail constraint-based contact method is presented. The constraint method deals efficiently with the two-point contact scenario. Equivalent profiles that maintain real wheelset kinematics are defined. A linear regularization for continuous points from tread to flange is derived. Contact forces are applied at the exact locations in the two-point contact scenario. Abstract: This paper presents a rigid contact approach to analyse the two-point wheel-rail contact scenario using the simplified constraint-based contact method called Knife-edge Equivalent Contact method (KEC-method). The proposed approach makes use of the computationally efficient online solution of the KEC constraints, where a single-point rail is in contact with an equivalent wheel profile, and provides an exact relation between the location of the contact points in the equivalent and real profiles. In this context, the two-point contact scenario can be easily dealt by linearly softening the KEC-constraints in the vicinity of the two-point contact, that gives a continuous and unique contact point solution between each wheel-rail pair and avoids finite contact point jumps between tread and flange. This allows an efficient kinematic solution of the two-point contact scenario. However, to properly account for a dynamic equivalence of the two-point contact scenario in the computation of the tangential contact forces, the reaction force acting on the wheel when the contact point lies on the tread-flange transition, is transformed into two contact forces acting on the tread and flange respectively maintaining the resultant equilibrium of forces at the wheel.